Brainstem evoked auditory potentials with speech stimulus in the auditory processing disorder - Filippini,Renata (2009)
Although the clinical use of click stimuli to assess auditory function at the brainstem is already established, and numerous research projects use such stimuli to study human hearing, little is known about the auditory processing of a complex stimulus like speech. AIM: This study aimed at validating the speech stimulus as an effective method to evaluate speech auditory processing, to help us better understand its disorders. MATERIALS AND METHODS:This prospective clinical study tested 20 subjects with Auditory Processing Disorders (APD) and 20 subjects with normal development (ND - control group) using the Brainstem Auditory Evoked Potentials with clicks and speech stimuli. The latter is based on first 40ms of the spoken syllable /da/. RESULTS: No differences were observed between the groups regarding the click stimulus. However, with the speech stimulus the APD group presented latency delay and lower amplitudes when compared to the ND group. CONCLUSION: Speech stimulus proved to be more sensitive for the evaluation of Auditory Processing Disorders, showing possible alterations in synchronicity and speech processing neural input speed, especially as to the linguistic information of the latter.